Hol tart a közép-kelet-európai kockázati- és magántőke-piac öt évvel a válság után? - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– While in Western Europe the venture capital and private equity industry have mostly got over the shock of the crisis, the Central and East-European region in 2013 still showed a tendency of deterioration. Signs of recovery could not be perceived neither in fundraising, investment or divestment activities. Similarly to Europe in general, institutional investors wishing to invest in the CEE region are concerned by the increasing north-south divergence. In Hungary substantial government venture capital resources are available for early-stage venture capital investments. However, in addition to the general problems affecting the CEE region, the freezing of buy-outs can be attributed to special difficulties arising from special economic policy risks in Hungary.
Keywords: G23; G24; G28; M13; 330; venture capital; private equity; SME finance; Central and Eastern Europe